2023
DOI: 10.21037/qims-22-539
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence with a deep learning network for the quantification and distinction of functional adrenal tumors based on contrast-enhanced CT images

Abstract: Background: Functional adrenal tumors (FATs) are mainly diagnosed by biochemical analysis. Traditional imaging tests have limitations and cannot be used alone to diagnose FATs. In this study, we aimed to establish an artificially intelligent diagnostic model based on computed tomography (CT) images to distinguish different types of FATs. Methods: A cohort study of 375 patients diagnosed with hyperaldosteronism (HA), Cushing's syndrome (CS), and pheochromocytoma in our center between March 2015 and June 2020 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Some studies have shown that the performance of models using multiphase images is higher than that of those using single-phase images ( 37 - 39 ). In this experiment, we used AIMS to build radiomics models with features extracted from multiphase images for ccRCC Fuhrman grading.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that the performance of models using multiphase images is higher than that of those using single-phase images ( 37 - 39 ). In this experiment, we used AIMS to build radiomics models with features extracted from multiphase images for ccRCC Fuhrman grading.…”
Section: Resultsmentioning
confidence: 99%
“…Subclinical CPA is the most common functional adrenal tumors ( 7 ), while as many as 30% of APA patients manifest the similar clinical symptoms as CPA because of hypokalemia ( 8 , 9 ); which makes it particularly difficult to distinguish between the two from a clinical perspective. Furthermore, 10–20% of ACAs occur bilaterally or with multiple lesions ( 3 , 10 ), functional diagnosis is challenging when the responsible lesion needs to be accurately located ( 3 , 8 , 11 ). Percutaneous cannulation of the adrenal vein is the “gold standard” for APA diagnosis, but the difficulty, cost and invasiveness of the procedure limit its widespread use in clinical practice ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In traditional imaging examinations, the evaluation is mainly based on the size, density, border and enhancement degree of the tumor, helping radiologists and clinicians distinguish whether adrenal masses are adenomas or non-adenomas. Further differentiating the function of ACA as APA or CPA is not available ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of imaging techniques and the popularization of abdomen CT scanning for physical examination, the detection rate of adrenal incidentalomas is increasing [ 2 4 ]. Adrenal adenomas account for the majority of adrenal incidentalomas (41–52%), followed by metastatic tumors (19%), myelolipoma (9%), and pheochromocytoma (8%) [ 5 ]. Although up to 80% of these tumors are benign, sPHEO can cause life-threatening hypertension during surgery, which can lead to serious cardiovascular events [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%